Peran Ganda Guru Pendidikan Agama Islam dalam Membimbing Siswa Bermasalah di SD Islam Al-Rasyid Pekanbaru - Aulia Fitri; Wismanto Wismanto; Mukh Nursikin; Mashuri Mashuri; Khairul Amin (Journal on Education, 2023)
This study aims to find out the dual role played by PAI teachers in guiding students with problems, knowing the concrete efforts of activity programs carried out by PAI teachers in dealing with problematic students, knowing the cooperation between PAI teachers and homeroom teachers in helping students with problems because there are no BP teachers in this school. and to find out the supporting and inhibiting factors in dealing with troubled students at SD Islam al-Rasyid Pekanbaru. The research which was conducted for 3 months (October-December) used qualitative methods and data collection techniques in the form of observation, interviews, and documentation at SD Islam al-Rasyid Pekanbaru. The subjects of this study were school principals, PAI teachers, homeroom teachers, and students at SD Islam al-Rasyid Pekanbaru. The results of this study place the role of the PAI teacher as a religious teacher who should be admired and emulated and the role of the PAI teacher as a counseling teacher in providing guidance to problem students at SD Islam al-Rasyid Pekanbaru by implementing exemplary, habituation and advice methods. In addition, the factors that support Islamic Religious Education teachers in dealing with problem students are due to spiritual activities, while the inhibiting factor is the limited time that Islamic Religious Education teachers have in carrying out their duties to overcome student problems.